Differentiation of duck wing buds grafted on the chorioallantoic membrane (CAM). - Simon, Mona Gilda B
Stage 20 (3 1/2 day) duck limb buds grafted on the chorioallantoic membrane (CAM) exhibited abbreviated structure of the pectoral girdle and/or the humerus in most of the extant specimens, except for one which displayed a normal cartilaginous humerus. No skeletal structure distal to the humerus were formed in CAM transplants. Similarly staged flank transplants showed morphologically distinct skeletal structures of the entire duck wing, akin to the control (normal)limbs. The results suggest that CAM, an extraembryonic tissue, is not capable of providing all the influences needed for the determination and elaboration of skeletal wing structures.